Filamentous phages of Ralstonia solanacearum: double-edged swords for pathogenic bacteria - Yamada, Takashi (Frontiers in Microbiology, 2013)
Some phages from genus Inovirus use host or bacteriophage-encoded site-specific integrases or recimbinases establish a prophage state. During integration or excision, a superinfective form can be produced. The three states (free, prophage, and superinfective) of such phages exert different effects on host bacterial phenotypes. In Ralstonia solanacearum, the causative agent of bacterial wilt disease of crops, the bacterial virulence can be positively or negatively affected by filamentous phages, depending on their state. The presence or absence of a repressor gene in the phage genome may be responsible for the host phenotypic differences (virulent or avirulent) caused by phage infection. This strategy of virulence control may be widespread among filamentous phages that infect pathogenic bacteria of plants.